Evaluation of effective factors in the failure of combining plans in rural regions (Case study: Sharm town, Kermanshah province) - Mehdi Taleb; Hossain Merzaei; Afwat Naderi (مسکن و محیط روستا)
Rural development planning as a mechanism for rural development requires a precise understanding of the needs and condition of rural communities. Combining villages has been one of the policies developed and implemented in post-war reconstruction projects as well as rural development projects in Iran. During the post-war reconstruction period, Shram town plan was developed with the aim of combining three villages namely Hanigarmalah, Kaymneh and Bidarwaz (Kermanshah province). Despite planning initiatives and efforts, villagers either moved to other cities or villages or moved back to their destroyed villages instead of moving to the new town. This study evaluates the economic, socio-cultural, and physical causes of the failure in plans and projects that involve combining villages, focusing on the case of Shram. This evaluation relies on the existing social theoretical frameworks in the literature including theories of participatory rural development as well as scholarly debates on combining rural settlements. Techniques of data gathering adopted in this research include deep interview, field observation as well as document review. Overall 39 interviews with opponents and proponents of Shram town plan as well as local authorities have been conducted. Aside from identifying the causes of the failure of the town plan, this research found that an appropriate planning mechanism and utilizing the capacities of villagers can prepare the ground for developing successful plans and projects of combining rural settlements. On this basis and in order to reach a common understanding and shared points of views between the stakeholders, it is necessary for planners to build positive and constructive relations with villagers. Additionally, unlike current approaches in similar plans and projects, which heavily rely on spatial and physical approaches, it is necessary to pay attention to social, economic and cultural dimensions of such plans and adopt a more holistic approach in planning and implementation.